Teaching Robotics in Pandemic Times Through Remote Education - Silva, Raphael de Abreu Alves e; Joventino, Carlos Fernando; Pereira, Jonathas H. M.; Correa, Lucas Pinheiro (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
During the COVID-19 pandemic, several challenges appeared before everyone. One of the biggest impacts that were observed was on education as a whole. The need for social distance and remote classes directly impacted teaching. Especially in matters of technology there were some more difficulties that needed to be overcome. In this article we will see an experience of how to teach robotics remotely at the IFSP/RGT in an accessible way to students and as a motivating tool during the period of remote classes.